DECONSTRUCTION OF GENDER STEREOTYPES THROUGH HUMOR: A QUALITATIVE STUDY ON TIKTOK ACCOUNTS @FAKBOIBERKELAS8 - Faizin, Moch. Nur; Febriana, Poppy (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study analyzes how the TikTok account @fakboiberkelas8 employs humor and satire to deconstruct gender stereotypes and reshape public perceptions of gender identity. Method: Utilizing Jacques Derrida’s deconstruction framework, data were collected from video content and selected comments on the account, focusing on how humorous narratives engage with dominant gender discourses. Results: The findings reveal that @fakboiberkelas8 consistently subverts conventional gender stereotypes through parody and satire, particularly by challenging narratives that position men in subordinate roles within digital social interactions. The account reconstructs male identity as critical of gender inequality while maintaining an entertaining and relatable tone. Everyday scenarios are frequently used to highlight the absurdity of entrenched stereotypes, making the critique accessible to a broad audience. Novelty: This research contributes to media and gender studies by demonstrating the role of humorous digital content as a persuasive tool for dismantling gender norms. It underscores the unique potential of TikTok as a platform where entertainment and critical discourse intersect, positioning humor not merely as entertainment but as an effective medium for fostering critical reflection on gender identity.